Risk Patterns of Distant Metastases in Follicular, Papillary and Medullary Thyroid Cancer - Machens, Andreas; Lorenz, Kerstin; Weber, Frank; Dralle, Henning (Hormone and Metabolic Research, 2021)
This study of 542 patients with follicular thyroid cancer, 366 patients with the follicular variant and 1452 patients with the classical variant of papillary thyroid cancer, and 819 patients with sporadic medullary thyroid cancer operated at a tertiary referral center aimed to determine risk patterns of distant metastasis for each tumor entity, which are ill-defined. On multivariable logistic regression analyses, lymph node metastasis consistently emerged as an independent risk factor of distant metastasis, yielding odds ratios (ORs) of 2.4 and 2.8 for follicular thyroid cancer and the follicular variant of papillary thyroid cancer, and ORs of 5.9 and 6.4 for the classical variant of papillary thyroid cancer and sporadic medullary thyroid cancer. Another independent risk factor consistently associated with distant metastasis, most strongly in follicular thyroid cancer and the follicular variant of papillary thyroid cancer (OR 3.5 and 4.0), was patient age >60 years. Altogether, 2 distinct risk patterns of distant metastasis were identified, which were modulated by other cancer type-dependent risk factors: one with lymph node metastasis as leading component (classical variant of papillary thyroid cancer and sporadic medullary thyroid cancer), and another one with age as leading component (follicular thyroid cancer and the follicular variant of papillary thyroid cancer). Distant metastasis was exceptional in node-negative patients with sporadic medullary thyroid cancer (1.7%) and the classical variant of papillary thyroid cancer (1.4%), and infrequent in node-negative patients with the follicular variant of papillary thyroid cancer (4.4%). These findings delineate windows of opportunity for early surgical intervention before distant metastasis has occurred.
Keywords: thyroid carcinoma; primary tumor size; lymph node metastasis; distant metastasis; patient age; risk factor